2012
DOI: 10.1016/j.jcta.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Generalised quadrangles with a group of automorphisms acting primitively on points and lines

Abstract: We show that if G is a group of automorphisms of a thick finite generalised quadrangle Q acting primitively on both the points and lines of Q, then G is almost simple. Moreover, if G is also flag-transitive then G is of Lie type.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(107 citation statements)
references
References 20 publications
(36 reference statements)
0
107
0
Order By: Relevance
“…Theorem 2.1). For some results on flag-transitive generalized quadrangles, we refer to Bamberg et al [5]; for flag-transitive generalized hexagons, we refer to Schneider and Van Maldeghem [30].…”
Section: Lemma 54 Let π Be a Projective Plane Of Order Q With Q Evementioning
confidence: 99%
“…Theorem 2.1). For some results on flag-transitive generalized quadrangles, we refer to Bamberg et al [5]; for flag-transitive generalized hexagons, we refer to Schneider and Van Maldeghem [30].…”
Section: Lemma 54 Let π Be a Projective Plane Of Order Q With Q Evementioning
confidence: 99%
“…Note that the regular hyperoval of PG(2, 2) does not appear in Corollary 1.5 because it does not yield a thick generalized quadrangle (see Section 5). Note also that if H is the regular hyperoval of PG (2,4), then T * 2 (H) is the unique generalized quadrangle of order (3,5) [20, 6.2.4].…”
Section: Corollary 15mentioning
confidence: 99%
“…By contrast, C acts regularly on a conic in PG (2,8), and fixes the nucleus. Identifying the vectors of V (3,8) with those of V (9, 2), we see that the fixed-point space of C is a 3-dimensional F 2 -subspace. This contradiction proves our claim.…”
Section: Remark 33mentioning
confidence: 99%
“…Assume Hypothesis 4.1. If G acts with type HA on P, then Q is the unique generalized quadrangle of order (3,5).…”
Section: Quasiprimitive On Points But Not Linesmentioning
confidence: 99%
“…If Q is a finite flag-transitive generalized quadrangle and Q is not a classical generalized quadrangle, then (up to duality) Q is the unique generalized quadrangle of order (3, 5) or the generalized quadrangle of order (15, 17) arising from the Lunelli-Sce hyperoval.Finite generalized polygons satisfying stronger symmetry assumptions, such as the Moufang condition [15] or distance-transitivity [12,28], have been classified. The current state-of-the-art for generalized quadrangles is the classification of antiflag-transitive finite generalized quadrangles in [5], where it was shown that, up to duality, the only nonclassical antiflag-transitive generalized quadrangle is the unique generalized quadrangle of order (3,5). (An antiflag is a non-incident point-line pair.)…”
mentioning
confidence: 99%